Coupled/decoupled spray simulation comparison of the ECN spray a condition with the Σ-Y Eulerian atomization model. (April 2016) - Desantes, J.M.; García-Oliver, J.M.; Pastor, J.M.; Pandal, A.; Baldwin, E.; Schmidt, D.P.
Highlights: Σ -Y Eulerian model has been applied to the study of direct injection diesel sprays. A novel constraint on turbulent driven mixing multiphase flows is introduced. 3D and 2D coupled, and 2D decoupled simulations have been performed. Internal and external flow calculations can be performed independently. Internal nozzle flow effects appear in the near-field but vanish downstream. Abstract: This work evaluates the performance of the Σ -Y Eulerian atomization model at reproducing the internal structure of a diesel spray in the near-field. In the study, three different computational domains have been used in order to perform 3D and 2D coupled simulations, where the internal nozzle flow and external spray are modeled in one continuous domain, and 2D decoupled simulations, where only the external spray is modeled. While the 3D simulation did the best job of capturing the dense zone of the spray, the 2D simulations also performed well, with the coupled 2D simulation slightly outperforming the decoupled simulation. The similarity in results between the coupled and the decoupled simulation show that internal and external flow calculations can be performed independently. In addition, the use of spatially averaged nozzle outlet conditions, in the case of an axisymmetric (single-hole) convergent nozzle, leads to a slightly worse near-field spray predictions but to an accurate far-field ones. Finally, a novel constraint on turbulent driven mixing multiphase flows is introduced which prevents the slip velocity from exceeding the magnitude of the turbulent fluctuations through a realizable Schmidt number. This constraint increased model stability, allowing for a 4x increase in Courant number.